PERANAN BIROKRASI DALAM MENINGKATKAN DAYA SAING DAN INVESTASI DI DAERAH - Murtir jeddawi (Universitas Trisakti, 2009)
The purpose of this article is to analyze the role of local bureaucracy in increasing competitiveness and local investment. Research method is library research.The result show that bureaucracy is a central influenced in increasing competitiveness and local investment. But in local autonomy era now cultural in bureaucracy has not shown optimal result yet, even if in some competitiveness areas and local investment were increased and growth in significant.Keywords : Bureaucracy, investment, Competitiveness